Adolescents' Online Connections with Friends during COVID-19: An Assessment of the Forms of Communication and Their Association with Emotional Adjustment - Allie M. Spiekerman; Yue Guo; Jessica Payton; Nicole Campione-Barr; Sarah E. Killoren; Wendy M. Rote; Amanda J. Rose (MDPI AG, 2023)
The COVID-19 pandemic and subsequent stay-at-home orders limited adolescents' ability to connect with friends in person, leading adolescents to rely on digital forms of communication to interact with friends. The present study (N = 168 adolescents ages 11-20, 51.40% female) examined the types of digital communication adolescents used to connect with friends during the pandemic stay-at-home orders and how each form of digital communication related to adolescents' emotional adjustment. The results showed texting to be the most common way adolescents connected with friends. Boys were more likely than girls to talk with friends through social gaming. Synchronous forms of communication (i.e., texting, video calls, and social gaming) were associated with reduced loneliness and depressive symptoms and higher flourishing. Connecting with friends by posting or responding on social media was not associated with adolescent well-being. These results suggest that forms of digital communication that allowed adolescents to talk with friends in real time were particularly important for adolescents' emotional well-being during the COVID-19 pandemic.